Effect of Using Computer in Getting and Remaining Information at Students of First Stage in Biology Subject (Journal Of Educational and Psychological Researches, 2013)
Effect of Using Computer in Getting and Remaining Information at Students of First Stage in Biology Subject MIAAD NATHIM RASHEED LECTURER Abstract The recent research goal is to know the influence of computer use to earn and fulfillment information for students of first class in biology material and to achieve that put many of the zeroing hypothesis by researcher as follow: There were no differences between statistical signs at level (0,05) between the average students' marks who they were study by using computer and between the average student ' marks who they were study in classical method of earning and fulfillment. The researcher chose the intentional of the medical technical institute that included of two branches the first class (A) for experimental group and branch (B) for controlled group as realty of (60) students (females and males) in every branches and because I was as statistics so the differentiate between explanation students' research group in use of the researcher limit scientific material of (third unit for biology material), researcher has modeled statistical test consists of (50) clauses from multi selection type showed for specialized group of test adding to know the distinguish between every clauses by using the half portion method and upon the contrast coefficient that among of (84.0) and after the finish of applied experiment of statistical test by using the dual independent samples test. And the obtained results, researcher concluded the use of computer as motivation for the students to do homework of the teaching biology material and she suggested to do their studies in another variables of non earing and fulfillment.